2008
DOI: 10.2137/145960606778644494
|View full text |Cite
|
Sign up to set email alerts
|

Spring barley yield and nitrogen recovery after application of peat manure and pig slurry

Abstract: The effectiveness of peat manure, manufactured of pig slurry and moderately humified Sphagnum peat (slurry:peat ca. 1:1.5 v/v), as nitrogen (N) source for spring barley was investigated in a four-year field experiment on a clay loam soil in south-western Finland. Pig slurry, NPK fertilizer and plain peat were used as references. Manures were incorporated before sowing or surface-applied after sowing in spring at an ammoniacal N rate of 54-106 kg ha -1 with or without supplementary NPK fertilizer (40 kg N ha -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The experiment had four replications. The details of the experiment are reported by Mattila (2006). Weather data ( Fig.…”
Section: Nitrogen In Soil and Cropmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment had four replications. The details of the experiment are reported by Mattila (2006). Weather data ( Fig.…”
Section: Nitrogen In Soil and Cropmentioning
confidence: 99%
“…In Finland, a country with large peat resources, peat has been used traditionally as a bedding material for domestic animals on some farms. A new way to use peat is to mix it with animal slurry to enable the storing of manure in a solid form, when the storage capacity for slurry is insufficient (Mattila 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shallow disk injection is a manure application method used in no‐till systems to incorporate manure into the soil with minimal soil disturbance. Although injection manure methods require specialized equipment and are slower than broadcasting manure (Johnson, Kleinman, Beegle, Elliott, & Saporito, 2011), manure injection may increase N availability to plants because of manure N conservation and placement near roots (Mattila, 2006). In previous studies, shallow injection of swine ( Sus scrofa domesticus L.) slurry immediately before crop seeding increased N agronomic efficiency and apparent N recovery (ANR) of corn and wheat ( Triticum aestivum L.) compared to broadcast manure in a Brazilian no‐till production system (Gonzatto et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…1). Surface application can reduce corn yields by up to 14% (Mattila, 2006) because of increased N loss through ammonia volatilization, which reduces overall N agronomic efficiency (Gonzatto et al, 2017). The benefits from injection may be dependent on time of application, as Safley et al (1980) reported that yield increases were higher in late winter than in fall or midwinter.…”
Section: Resultsmentioning
confidence: 99%